Setting Transparent Expectations for Successful Group Work - Cecilia E. Suarez; Jarred A. Shellhouse (EDIS)
Regardless of workspace or class setting, group work has gotten a reputation for being less than pleasant. However, when individuals have the opportunity to prepare for group work via understanding their personal strengths, expectations, and perspectives, the not-so-popular group work can often turn into pleasant, productive, and collaborative engagement. Because group dynamics shift and vary from group to group, there is a constant learning opportunity to understand how to work in groups successfully. This new 2-page publication of the UF/IFAS Department of Agricultural Education and Communication will identify simple yet effective strategies that can serve as foundational building blocks whenever preparing oneself or others for group work. Written by Cecilia E. Suarez and Jarred A. Shellhouse. https://edis.ifas.ufl.edu/wc389